Pete the Cat: 5-minute bedtime stories - Dean, Kim 1969-; Dean, James 1957- (Harper, an imprint of HarperCollinsPublishers, 2020)
Snuggle up with your favorite blue cat in these twelve groovy bedtime adventures! Join Pete the Cat as he hosts a fun slumber party, helps the tooth fairy, camps out in the wilderness, and so much more. Each of these stories is an ideal length for reading aloud in about five minutes, which means this collection is the absolutely perfect addition to your bedtime tradition
A compilation of stories previously published separately between 2015 and 2018. All of them were written by James Dean except Pete the Cat and the bedtime blues written by Kim Dean
Reader for children
Keywords: Pete / the Cat (Fictitious character) / Children's fiction; Cats / Children's fiction; Animals / Children's fiction; Bedtime / Children's fiction; Animals; Baking; Bedtime; Books and reading; Camping; Caterpillars; Cats; Cooperativeness; Fire fighters; Friendship; Interplanetary voyages; Libraries; Lost articles; Mothers and sons; Pirates; Railroad travel; Sasquatch; School field trips; Schools; Sleepovers; Teachers; Tooth Fairy (Legendary character); Treasure troves; Tree houses; Readers; Humorous fiction; Picture books; Short stories; Anthologie; Bilderbuch